(untitled) (Mustansiria Dental Journal, 2018)
Background: the purpose of this retrospective study was to compare some craniofacral cephalometric measurements and arch width dimensions between subjects with class II division 1 and class II division 2 malocclusion in Iraqi population. Materials and methods: 60 digital true lateral cephalometric radiographs 30 for class II division 1 and 30 for class II division 2 subjects (15 males, 15 females for each group ) were selected from the files of the patients attending the orthodontic clinic in the college of dentistry, university of Baghdad with an over jet more than 6 mm and class II molar and canine relation. Also for each group a study model were take to measure the arch width for both upper and lower arches. The inter molar, inter premolar and inter canine measurements were carried out on study models. The radio graphs were digitized by using the Auto CAD program in the personal computer all the data compared by independent t- test. Results and conclusions: For the dental arch width measurements the statistically significant difference was found between the mandibular inter canine width and maxillary inter molar width. The cephalometric results that class II division 1 showed a retrognathic mandible, and this due to the difference in SNB angle between the two groups, the class II division 2 subjects had anterior position of the mandible relative to the cranial base, more concave profile, great posterior face height, horizontal growth, the mandibular inclination is interiorly, more deep bite, and reduction in the mandibular inter canine width and maxillary inter molar width .